Impact of Changes in Perinatal Care on Neonatal Respiratory Outcome and Survival of Preterm Newborns: An Overview of 15 Years - Filipa Flor-de-Lima; Gustavo Rocha; Hercília Guimarães (Critical Care Research and Practice)
Survival and outcomes for preterm infants with respiratory distress syndrome (RDS) have improved over the past 30 years. We conducted a study to assess the changes in perinatal care and delivery room management and their impact on respiratory outcome of very low birth weight newborns, over the last 15 years. A comparison between two epochs was performed, the periods before and after 2005, when early nasal continuous positive airway pressure (NCPAP) and Intubation-SURfactant-Extubation (INSURE) were introduced in our center. Three hundred ninety-five clinical records were assessed, 198 (50.1%) females, gestational age 29.1 weeks (22–36), and birth weight 1130 g (360–1498). RDS was diagnosed in 247 (62.5%) newborns and exogenous surfactant was administered to 217 (54.9%). Thirty-three (8.4%) developed bronchopulmonary dysplasia (BPD), and 92 (23%) were deceased. With the introduction of early NCPAP and INSURE, there was a decrease on the endotracheal intubation need and invasive ventilation (P<0.0001), oxygen therapy (P=0.002), and mortality (P<0.0001). The multivariate model revealed a nonsignificant reduction in BPD between the two epochs (OR=0.86; 95% CI 0.074–9.95; P=0.9). The changes in perinatal care over the last 15 years were associated to an improvement of respiratory outcome and survival, despite a nonsignificant decrease in BPD rate.